SAR changes in a human head model for plane wave exposure (500 - 2500 MHz) and a comparison with IEEE 2005 safety limits - (:unkn) unknown (International Microwave Power Institute, 2008)
In this paper, external electric field values that are derived from the largest peak average 10 g SAR (Specific Absorption Rate) results in a realistic human head model are compared with current IEEE and ICNIRP reference levels. The head is illuminated by a plane wave source at seven different frequencies ranging from 500 MHz to 2500 MHz, with five different incident directions and three polarizations. Results reveal that the presence of metallic wire spectacles reduces the external electric field levels in the region above 900 MHz. Comparison of derived electric field values shows that the current IEEE and ICNIRP safety limits provide a conservative estimate.
Keywords: Finite difference time domain (FDTD) method; RF exposure; Safety limits; Specific absorption rate (SAR)